OPTIMIZATION MODELLING OF ENGINEERING ENTERPRISES FINANCIAL SECURITY IMPROVEMENT - Oriekhova, Kateryna; Kendiukhov, Oleksander; Zakharkin, Oleksii; Solodovnik, Olesia; Zakharkina, Liudmyla; Murovana, Tetiana (Journal of Applied Engineering Science, 2021)
The article's purpose is to develop a methodical approach to improving financial security, which takes into account the acceleration of reproducing processes on Ukraine's device of engineering enterprises. This approach is based on multi-cellular vector optimization. It allows us to determine the optimal values of current assets' manifestations and net profit dynamics and set the optimal correlation between them.Approbation of a methodical approach to improving financial security and acceleration of reproducing processes on the example of Ukraine's four engineering enterprises was performed. Financial statement data for eight periods were used to build optimization vectors. To improve financial security and accelerate the reproducing processes of Ukraine's engineering enterprises, certain volumes of working assets, periods of their turnover, their marginal value taking into account different financing sources, and maximum net profit at certain manifestations of the dynamics of current assets are established.In implementing the methodical approach to improving financial security and accelerating the reproducing processes in engineering enterprises' practical activities, highly qualified personnel occupy a significant role and place. The powerful toolkit of their provision is material stimulation (an increase of wages, provision of premiums) and establishment of relations in the team (social justice in the department); the opportunity to advance on the career ladder; respect for employees by management; frank and friendly relationships at all levels of management; participation in corporate holidays of all employees. Therefore, the study's further direction is developing a methodical approach to improving the financial security of engineering enterprises, taking into account personnel support.
Keywords: engineering enterprises; optimization modeling; financial security; methodical approach; net profit